Iowa Birdline update, December 10, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Email of the Iowa Birdline update for December 10, 1990. Highlights of the update include the continued presence of a Yellow Grosbeak and sightings of Black-legged Kittiwakes and Bohemian Waxwings. Also included are handwritten notes with a sighting of several thousand Gulls at Lake Red Rock and a report of very unusual appearance of a Hepatic Tanager in Pleasant Valley. Epson - sheet feed/flatbed